2022
DOI: 10.1128/spectrum.01677-22
|View full text |Cite|
|
Sign up to set email alerts
|

Chemotherapeutic Drugs Induce Different Gut Microbiota Disorder Pattern and NOD/RIP2/NF-κB Signaling Pathway Activation That Lead to Different Degrees of Intestinal Injury

Abstract: Chemotherapy-induced intestinal injury limits the clinical use of drugs. Intestinal injury involves multiple signaling pathways and gut microbiota disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…It has previously been shown that Candidatus Saccharimonas was the most abundant genera in colitis-associated CRC, and it was also associated with other inflammatory diseases . For instance, Candidatus Saccharimonas was positively correlated with nucleotide-binding oligomerization domain (NODs)/receptor-interacting protein 2 (RIP2)/NF-κB signaling pathway in redundancy (RDA)/canonical correspondence (CCA) analyses . CUR and AC reduced Candidatus Saccharimonas abundance, indicating their beneficial effect on CRC (Figure E).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has previously been shown that Candidatus Saccharimonas was the most abundant genera in colitis-associated CRC, and it was also associated with other inflammatory diseases . For instance, Candidatus Saccharimonas was positively correlated with nucleotide-binding oligomerization domain (NODs)/receptor-interacting protein 2 (RIP2)/NF-κB signaling pathway in redundancy (RDA)/canonical correspondence (CCA) analyses . CUR and AC reduced Candidatus Saccharimonas abundance, indicating their beneficial effect on CRC (Figure E).…”
Section: Discussionmentioning
confidence: 81%
“…38 For instance, Candidatus Saccharimonas was positively correlated with nucleotidebinding oligomerization domain (NODs)/receptor-interacting protein 2 (RIP2)/NF-κB signaling pathway in redundancy (RDA)/canonical correspondence (CCA) analyses. 39 CUR and AC reduced Candidatus Saccharimonas abundance, indicating their beneficial effect on CRC (Figure 7E). In comparison, Bacteroides and Eubacterium nodatum group abundances were elevated in the LAC group, which might be associated with the ameliorative effect of low AC doses (Figure 7G).…”
Section: Discussionmentioning
confidence: 90%
“…[ 64 ] However, the mechanisms through which 5‐FU triggers gut microbiota dysbiosis and how dysbiosis exacerbates 5‐FU‐induced intestinal mucositis required further investigation. [ 65 ] Our study showed that 5‐FU might contribute to the destruction and functional decline of intestinal epithelial cells by toxicity‐induced apoptosis and that this destruction might lead to the loss of Muc2, which is the main protein in the mucous layer, thereby preventing the establishment of a stable gut microbiota. [ 66 ] Furthermore, the deficiency of Reg3b, an antimicrobial peptide, disrupts the balance between beneficial and pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“… 228 Moreover, Streptococcus exhibited a compelling correlation with the NOD/RIP2/NF-κB signaling cascade, and this intricate interplay could be modulated by several chemotherapeutic agents. 229 Baraniya et al 230 found the transcriptional alterations caused by Streptococcus mitis primarily exhibited an anticancer effect, marked by the inhibition of the HOTAIR regulatory pathway, JAK/STAT signaling, Cyclin/Cyclin-dependent kinases, and endothelin1 signaling pathways. Neutrophil extracellular traps (NETs), intricate lattice-like structures composed of DNA-histone complexes and proteins discharged by activated neutrophils, were initially identified for their essential involvement in antimicrobial resistance and immune regulation.…”
Section: Overview Of Oral Microbiota In Carcinogenesismentioning
confidence: 99%